Serine racemase deficiency attenuates choroidal neovascularization and reduces nitric oxide and VEGF levels by retinal pigment epithelial cells. Issue 3 (13th October 2017) - Jiang, Haiyan; Wu, Mengjuan; Liu, Yimei; Song, Liping; Li, Shifeng; Wang, Xianwei; Zhang, Yun‐feng; Fang, Junxu; Wu, Shengzhou
Abstract: Choroidal neovascularization (CNV) is a leading cause of blindness in age‐related macular degeneration. Production of vascular endothelial growth factor (VEGF) and macrophage recruitment by retinal pigment epithelial cells (RPE) significantly contributes to the process of CNV in an experimental CNV model. Serine racemase (SR) is expressed in retinal neurons and glial cells, and its product, d ‐serine, is an endogenous co‐agonist of N ‐methyl‐d ‐aspartate receptor. Activation of the receptor results in production of nitric oxide ( . NO), a molecule that promotes retinal and choroidal neovascularization. These observations suggest possible roles of SR in CNV. With laser‐injured CNV mice, we found that inactivation of SR‐coding gene ( Srr null ) significantly reduced CNV volume, neovascular density, and invading macrophages. We exploited the underlying mechanism in vivo and ex vivo . RPE from wild‐type (WT) mice expressed SR. To explore the possible downstream target of SR inactivation, we showed that choroid/RPE homogenates extracted from laser‐injured Srr null mice contained less inducible nitric oxide synthase and decreased phospho‐VEGFR2 compared to amounts in WT mice. In vitro, inflammation‐primed WT RPEs expressed more inducible NOS, produced more . NO and VEGF than did inflammation‐primed Srr null RPEs. When co‐cultured with inflammation‐primed Srr null RPE, significantly fewer RF/6A‐a cell line of choroidal endothelial cell, migrated to the opposite side of the insert membrane than did cells co‐cultured with pre‐treated WT RPE. Altogether, SR deficiency reduces RPE response to laser‐induced inflammatory stimuli, resulting in decreased production of a cascade of pro‐angiogenic cytokines, including . NO and VEGF, and reduced macrophage recruitment, which contribute synergistically to attenuated angiogenesis. Abstract : We have demonstrated that serine racemase deficiency leads to attenuated choroidal neovascularization when subjected to laser photocoagulation. Serine racemase deficiency leads to inhibited AKT/PKB, ending up with blunting NFκB/iNOS/NO/HIF/VEGF signaling in retinal pigment epithelial cells when subjected to inflammatory stimuli. Also, serine racemase deficiency reduces RPE's ability to recruit macrophage to adjacent laser‐injured spots. Altogether, serine racemase deficiency reduces RPE's responses to inflammatory stimuli and macrophage infiltration, culminating in attenuated choroidal neovascularization induced by laser photocoagulation.